A schematic representation of nanosuspension preparation by various approaches - GY SRAVANKUMAR; DR.BRAHMA REDDY; T SANDEEP; T MURALI KRISHNA; S SRINIVASRAO; V SAIKIRAN; T SRINIVASARAO (International Journal of Pharma and Bio Sciences, 2019)
The interest in the preparation and application of nanometer-sized materials is increasing due to their tremendous potential as a drug delivery system with wide range of applications. Recently, Nano scale systems have received much interest as a way to resolve solubility issues because of their cost-effectiveness and technical simplicity compared to liposome’s and other colloidal drug carriers. Nano suspensions have proven to be a better alternative over other approaches currently available for improving bioavailability of number of drugs with low solubility. Nano suspensions have been extensively developed for a wide range of drugs and have been evaluated for in vitro and in vivo applications by various routes: parenteral, oral, pulmonary, topical. They have also been used for drug targeting. Different preparation methods for Nano suspensions and their application are being reported and patented. In fact, the number of products based on Nano suspension in the market and under clinical study is higher than that of other nanotechnology-based applications. A surprisingly large proportion of new drug candidates emerging from drug discovery programs are water insoluble, and therefore poorly bioavailable, leading to abandoned development efforts. These so-called ’brick dust’ candidates can now be rescued by formulating them into crystalline Nano suspensions. Nano suspensions not only solve the problem of poor solubility and bioavailability but also alter the pharmacokinetics of the drug, thus improving safety and efficacy.